Digital Dashboards for Summative Assessment and Indicators Misinterpretation: A Case Study - Cisel, Matthieu (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
Over the last decade, teachers in France have been increasingly pressured to use digital learning environments, and to shift from grade-based to skill-based assessment. Educational dashboards, which measure student input electronically, could foster such a transition by providing insights into learners’ performances. However, such dashboards could also foster data misinterpretation during the summative assessment process, should the indicators that they display be used without a proper understanding of what they reflect. This article presents a methodology to detect potential mistakes in the interpretation of the indicators in the context of inquiry-based learning. During the design of a learning environment, we analyzed, through analytics and classroom observations in primary and middle schools, the issues that could arise from the use of a dashboard. Our data suggest that the amount of information practitioners needed to collect to make indicators relevant was burdensome, making the dashboard unfit for assessment purposes at the scale of a classroom.